The Design of Project Procurement Management to Improve Company Performance Project (Study Case: Warehouse Manufacture) - Mochammad Ravi Armanda Putra; Gatot Yudoko; Muhammad Hanafi (Publikasi Indonesia, 2025)
The Indonesian construction industry continues to face significant challenges related to project delays, especially in warehouse manufacturing projects. These delays often result in increased costs, reduced quality, and weakened stakeholder trust. This research aims to analyze the primary causes of delays in the warehouse construction project of PT. WMA and to design a procurement management framework that improves project performance. By conducting qualitative methods such as group discussions, the study identifies key contributing factors, including poor planning, weak interdepartmental coordination, supplier delays, and insufficient procurement monitoring. Root cause analysis was conducted using the Current Reality Tree (CRT), revealing that the lack of effective procurement management was the central issue. The study proposes a comprehensive procurement management framework based on the PMBOK 6th Edition, emphasizing the importance of planning, executing, and controlling procurement processes. Implementation of this framework is expected to reduce project delays and enhance the overall performance of construction projects. The findings not only contribute to academic knowledge but also provide practical recommendations for improving procurement practices in Indonesia’s construction sector.